Analisis Deskriptif Soal Ujian Nasional Matematika SMA Program IPA Tahun Ajaran 2015/2016 Ditinjau dari Aspek Kognitif TIMSS - Alifia, Nugrahaning Nisa, Prof. Dr. Budi Murtiyasa, M.Kom (2017)
On international level, Indonesia's mathematics achievement is still on a very low level. It has been proved by Indonesia's low ranking according to TIMSS 2015. Besides, education system in Indonesia has long used National Exam (Ujian Nasional) as a prior way to evaluate students' competence. However, average score of Mathematics subject in National Exam is the lowest of all. Furthermore, this research becomes very important to do. This research aims to analyze and describe the mapping of National Exam of Mathematics subject in Science program of Senior High School on academic year 2015/2016 according to TIMSS 2015 cognitive aspects. This research is a kind of qualitative one. Data collection method used in this research is documentation method. Result of the research shows that: 1) the mapping of National Exam of Mathematics subject in Science program of Senior High School on academic year 2015/2016 does not spread equitably according to TIMSS 2015 cognitive aspects. 2) Percentage difference of each cognitive aspect is far enough. In association with cognitive aspects, questions in the exam are divided into 3 cognitive aspects, they are, knowing, applying and reasoning. 3) The questions in National Exam of Mathematics subject in Science program of Senior High School on academic year 2015/2016 are dominated by knowing aspect with a percentage of 47.5%. While the percentage of applying aspect is 30% and reasoning is 22.5%. This research concludes that the mapping of National Exam of Mathematics subject in Science program of Senior High School on academic year 2015/2016 does not spread equitably according to TIMSS 2015 cognitive aspects. Keywords: cognitive aspect, TIMSS, National Exam Senior High School